A rapid, highly accurate method for quantifying CALR mutant allele burden in persons with myeloproliferative neoplasms. Issue 9 (October 2015) - Yao, Qiu-Mei; Zhou, Jiao; Gale, Robert Peter; Li, Jin-Lan; Li, Ling-Di; Li, Ning; Chen, Shan-Shan; Ruan, Guo-Rui
Abstract : Background: Calreticulin (CALR) mutations were recently identified in a substantial proportion of persons with essential thrombocythemia (ET) and with primary myelofibrosis (PMF) without JAK2 V617F . Consequently rapid, sensitive, and specific methods to detect and quantify these mutations are needed. Methods: We studied samples from 1088 persons with myeloproliferative neoplasms (MPNs) including 421 JAK2 V617F negative subjects with ET, PMF, polycythemia vera (PV), chronic myeloid leukemia (CML) and hyper-eosinophilic syndrome (HES). Detection of CALR exon 9 mutations was done by PCR amplification followed by fragment length analysis and direct sequencing. Dilution assays were used to determine CALR mutant allele burden. Results: We detected CALR mutations in blood and bone marrow samples from 152 subjects with ET and with PMF but not in samples from normal or persons with PV, CML, or HES. CALR mutant peaks were distinct from wild-type peaks and dilution experiments indicated a sensitivity level of 0.5–5% for a CALR mutant allele in a wild-type background. Diverse types of mutations were detected including deletions, insertions, and complex indels. All mutations were confirmed by direct sequencing. We also used dilution experiments to quantify mutant allele burden. We were able to reproducibly detect mutant allele levels as low 5% (0.5–5%) in a wild-type background. Conclusions: PCR amplification followed by fragment length analysis is a rapid, sensitive, and specific method for screening persons with MPNs for CALR mutations, especially those with ET and PMF and for estimating mutant allele burden.